1998
DOI: 10.1038/sj.onc.1201731
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor activation of NF-κB is mediated through IκBα degradation and intracellular free calcium

Abstract: The transcription factor NF-kB is normally sequestered in the cytoplasm by its inhibitory subunit IkB. Most extracellular signals activate NF-kB through a mechanism involving the phosphorylation and proteasomedependent degradation of IkB. EGF activates NF-kB in A-431 carcinoma cells, which overexpress EGF receptors and in mouse embryo ®broblasts, which have a normal complement of receptors. Supershift experiments indicate that the NF-kB complexes induced by EGF are composed of p50/p50 homodimers and p65/p50 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 35 publications
3
91
0
1
Order By: Relevance
“…The family of NF-kB transcription factors are typically activated by proinflammatory cytokines such as tumor necrosis factor (TNF)-a or IL1b, as well as by Toll-like receptor (TLR) ligands through extremely well defined signaling cascades (Box 2) [29]. Early studies demonstrated that EGF triggers NF-kB activation through the proteasome-mediated degradation of the inhibitory molecule IkBa in estrogen receptor ERanegative breast cancer cells and in lung cancer-derived cells [30,31]. Heregulin also triggers NF-kB activation through the IKK complex in ERa-negative and ERBB2-positive breast cancer cells [32].…”
Section: Molecular Mechanisms Linking Egfr Signaling To Nf-kb Activationmentioning
confidence: 99%
“…The family of NF-kB transcription factors are typically activated by proinflammatory cytokines such as tumor necrosis factor (TNF)-a or IL1b, as well as by Toll-like receptor (TLR) ligands through extremely well defined signaling cascades (Box 2) [29]. Early studies demonstrated that EGF triggers NF-kB activation through the proteasome-mediated degradation of the inhibitory molecule IkBa in estrogen receptor ERanegative breast cancer cells and in lung cancer-derived cells [30,31]. Heregulin also triggers NF-kB activation through the IKK complex in ERa-negative and ERBB2-positive breast cancer cells [32].…”
Section: Molecular Mechanisms Linking Egfr Signaling To Nf-kb Activationmentioning
confidence: 99%
“…This could be correlated with the increased level of epidermal growth factor family receptors (EGFR) in ERϪ cells (3,7,(8)(9)(10). Our previous results demonstrated that activation of NF-B is a downstream consequence of EGF-EGFR interaction (7).…”
mentioning
confidence: 95%
“…ABIN-mediated inhibition of constitutive NF-kB activity in EGFR-overexpressing A431 and DU145 tumour cells reduces their proliferation We next investigated whether ABINs also affect NF-kB activity in A431 epidermoid and DU145 prostate carcinoma cell lines, which rely on endogenous EGFR overexpression and signalling to sustain their growth and proliferation (Fan et al, 1993;Peng et al, 1996), and which already show high constitutive NF-kB activity (Sun and Carpenter, 1998;Gasparian et al, 2002;Meeran and Katiyar, 2008). As a result, stimulation with 1 ng/ml EGF, known to maximally induce the growth of these cell lines (Konger and Chan, 1993;El Sheikh et al, 2004), only marginally further increased the expression of an NF-kB-dependent luciferase gene (Figure 8a).…”
Section: Egfr-mediated Nf-kb Activation Is Inhibited By Abinsmentioning
confidence: 99%
“…In carcinoma cells that overexpress EGFR family members, EGF has been shown to induce IkBa degradation and NF-kB DNA binding (Sun and Carpenter, 1998;Biswas et al, 2000). Likewise, it has been shown that heregulin induces the IKK-dependent and NF-kB-mediated proliferation of ErbB2-overexpressing breast cancer cells (Biswas et al, 2004), and potentiates ErbB3-and ErB4-mediated NF-kB activation (Bhat-Nakshatri et al, 2002;Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%